Antimicrobial Resistance and Antimicrobial Use Associated with Laboratory-Confirmed Cases of Campylobacter Infection in Two Health Units in Ontario - Anne E Deckert; Richard J Reid-Smith; Susan E Tamblyn; Larry Morrell; Patrick Seliske; Frances B Jamieson; Rebecca Irwin; Catherine E Dewey; Patrick Boerlin; Scott A McEwen (Canadian Journal of Infectious Diseases and Medical Microbiology)
AIM: A population-based study was conducted over a two-year period in the Perth District (PD) and Wellington-Dufferin-Guelph (WDG) health units in Ontario to document antimicrobial resistance and antimicrobial use associated with clinical cases of laboratory-confirmed campylobacteriosis.